Comparing Formulaicity of Learner Writing through Phrase-Frames: A Corpus-Driven Study of Lithuanian and Polish EFL Student Writing - Juknevičienė, Rita; Grabowski, Łukasz (Research in Language, 2018)
Learner corpus research continues to provide evidence of how formulaic language is (mis)used by learners of English as a foreign language (EFL). This paper deals with less investigated multi-word units in EFL contexts, namely, phrase-frames (Fletcher 2002–2007), i.e. sets of n-grams identical except for one word (it is * to, in the * of). The study compares Lithuanian and Polish learner writing in English in terms of phrase-frames and contrasts them with native speakers. The analysis shows that certain differences between Lithuanian and Polish learners result from transfer from their native languages, yet both groups of learners share many common features. Most importantly, the phrase-frame approach highlights structural peculiarities of learner writing which are otherwise difficult to capture.